Distributed robust planning for new power system considering uncertainty and frequency security - Xinxin Zheng; Dahai Zhang; Zhaohong Bie; Xue Wu (Alexandria Engineering Journal)
The integration of renewable energy into the grid has increased the uncertainty of source load, posing challenges to the frequency safety of the power system. Energy storage systems (ESS) are one of the most prominent alternative solutions to alleviate the issues associated with renewable energy. Therefore, a new robust planning method for energy storage capacity allocation distribution in power systems considering uncertainty and frequency safety is proposed. Firstly, establish a system frequency model that provides frequency support for a fast frequency response energy storage system, and propose an improved segmented linearization algorithm to transform the constructed frequency safety constraints. Secondly, establish a two-stage optimization model for planning and operation under frequency safety constraints, aiming to minimize system costs under frequency safety constraints; Then, iterative solutions are obtained by using column and constraint generation algorithms. Finally, case studies show the feasibility of the proposed planning method.